Anthropometric features and postural reactions in children with scoliosis and scoliotic posture - Wilczyński, Jacek; Janecka, Sylwia; Wilczyński, Igor (Journal of Education, Health and Sport, 2017)
Introduction. The aim of the research was to analyze the correlation between the anthropometric features and postural reactions in children with scoliosis and scoliotic posture. Material and method. The study included 28 girls aged 7-18 years old with scoliosis and scoliotic posture. Respondents were selected intentionally. Children attended to the Interschool Centre of Corrective Exercises in Starachowice. Height measurements were made by anthropometer, and the measurement of body weight was made with electronic scale.Those reactions were examined by static-dynamic Tecnobody’s ST 310 Plus Stability System platform. Variables were verified in terms of normal distribution by Shapiro-Wilk test. Depending on the compatibility of variable distributions with normal distribution, and the value of skewness and kurtosis, parametric or non-parametric tests have been used. To determine the correlation between the anthropometric variables and postural reactions the Spearman's rank correlation coefficient has been used. The level of significance was p <0,05. Conclusions. In Romberg’s test with opened eyes (OE), there were no significant correlations between the anthropometric variables and postural reactions. However, in the study with eyes closed (CE), there were significant, inversely proportional correlations between the body height and FBSD, and between the body height and AFBS. Inversely proportional correlations are understandable, because a higher children are generally slightly older, and together with age in children has been observed the reduction of postural reactions (better balance). Analysis of relationships between BMI and postural reactions with eyes closed (CE) showed a significant directly proportional correlations only with Abs AY. Higher values of BMI corresponds to the higher values of Abs AY.